Acciones preventivas sobre extravasacion por medio de contraste en pacientes - Arias-Osorio, Jovita (2022)
Objective: To analyze scientific evidence on prevention measures related to contrast media extravasation in patients. Methodology: A literature review was conducted using 4 databases SciELO, Pubmed, Scopus and Google Scholar in the last ten years, including studies in English, Spanish and Portuguese published in full text indexed journals, carrying a critical analysis of each selected article, reflecting a matrix to sort and categorize. Results: of the 15 scientific articles of the results found show the need to provide the identification of the risk scale (low. mild moderate and high) The affected areas usually present benign lesions characterized by hypervolemia and localized erythema that tend to heal spontaneously without sequelae. However, severe lesions, such as compartment syndrome, can also occur. For these reasons, it is necessary to know the patients at risk, technical characteristics, early diagnosis and timely management of this complication. These are the basic skills that every specialist nursing professional should possess. Conclusions: Extravasation considered an indicator of quality-of-care service in nursing care, with which preventive, corrective and educational measures should be taken in the area where venous accesses are manipulated, an adequate choice of injection site, puncturing thick veins from the elbow crease towards proximal avoiding future complications to reduce the incidence as a zero objective.